Leer la lee desde una perspectiva estudiantil: tópicos en los ocho números publicados en el Magazín - Ramírez-Espinosa, José Luis (Lee La LEE, 2022)
Leer la lee desde una perspectiva estudiantil: tópicos en los ocho números publicados en el Magazín